EPIDEMI HUMAN IMMUNODEFICIENCY VIRUS (HIV) SEBAGAI POTENSI ANCAMAN BIOWEAPONS & BIOTERRORISM DI ASIA TENGGARA - Anggraini, Melaty; Irawan, Angga Danu Fadil (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Komputer Indonesia, 2017)
HIV is now more than a quarter-century old. The disease has killed 20 million people worldwide, and it is estimated that 40 million more are infected with HIV (human immunodeficiency virus), the virus that causes AIDS. As the potential securitization on „Health as Security Threat‟ The broad scale of the epidemic leads the United Nations Security Council to do historical effort by adopting 1308 resolution that not only stated health issue in the first time, but also specifically linked the spread of HIV and AIDS to nurture peace and global security. On this paper, the writer would analysis a potential of the HIV on